An easy-to-fabricate source measure unit for real-time DC and time-varying characterization of multi-terminal semiconductor devices. (6th January 2021) - Das, Avishek
Abstract: A versatile Arduino based source measure unit (ASMU) is fabricated for measuring both the DC and low-frequency AC electrical characteristics of multi-terminal semiconductor devices. The ASMU system is capable of bidirectional voltage sourcing and current measurement in all four quadrants. The system is programmed with the LabVIEW environment for real-time data acquisition. The voltage bias and current measurement range are observed to be ±4.65 V and ±14.6 mA with an optimum resolution of 5 mV and 7.8125 μ A, respectively. Both the two- and three-terminal passive and active devices can be characterized without changing any circuit configuration. The electronic and optoelectronic current-voltage, current-time, and transistor's input/output characteristics can be performed only by customizing the programming codes. The performance of the ASMU system is found to be highly comparable with commercial measurement systems. The experimental results suggest its potential application in characterizing semiconductor devices with maintaining adequate precision, cost-effectiveness, and low-power consumption.